Insights on the Excitation Spectrum of Graphene Contacted with a Pt Skin - Vito Despoja; Ivan Radović; Antonio Politano; Zoran L. Mišković (Nanomaterials, 2020)
The excitation spectrum in the region of the intraband (Dirac plasmon) and interband ( <semantics> π </semantics> plasmon) plasmons in graphene/Pt-skin terminated Pt <semantics> 3 </semantics> Ni(111) is reproduced by using an ab-initio method and an empirical model. The results of both methods are compared with experimental data. We discover that metallic screening by the Pt layer converts the square-root dispersion of the Dirac plasmon into a linear acoustic-like plasmon dispersion. In the long-wavelength limit, the Pt d electron excitations completely quench the <semantics> π </semantics> plasmon in graphene at about <semantics> 4.1 </semantics> eV, that is replaced by a broad peak at about 6 eV. Owing to a rather large graphene/Pt-skin separation (≈3.3 Å), the graphene/Pt-skin hybridization becomes weak at larger wave vectors, so that the <semantics> π </semantics> plasmon is recovered with a dispersion as in a free-standing graphene.